Eggs: the uncracked potential for improving maternal and young child nutrition among the world's poor. (7th May 2014) - Iannotti, Lora L; Lutter, Chessa K; Bunn, David A; Stewart, Christine P
<x xml:space="preserve">Abstract</x> Eggs have been consumed throughout human history, though the full potential of this nutritionally complete food has yet to be realized in many resource‐poor settings around the world. Eggs provide essential fatty acids, proteins, choline, vitamins A and B12, selenium, and other critical nutrients at levels above or comparable to those found in other animal‐source foods, but they are relatively more affordable. Cultural beliefs about the digestibility and cleanliness of eggs, as well as environmental concerns arising from hygiene practices and toxin exposures, remain as barriers to widespread egg consumption. There is also regional variability in egg intake levels. In Latin American countries, on average, greater proportions of young children consume eggs than in Asian or African countries. In China and Indonesia, nutrition education and social marketing have been associated with greater amounts of eggs in the diets of young children, though generally, evidence from interventions is minimal. Homestead chicken‐and‐egg production with appropriate vaccination, extension service, and other supports can simultaneously address poverty and nutrition in very poor rural households. With undernutrition remaining a significant problem in many parts of the world, eggs may be an uncracked part of the solution.